Synthesis of some novel benzimidazole derivatives and their biological evaluation - Gund, Dnyandev Radhu; Rao, Balivada Venkata Satyasai Varaprasad; Mandhare, Pandurang Narayanrao; Vaidya, Sanjay Dashrath (European Journal of Chemistry, 2015)
A series of novel benzimidazole derivatives have been synthesized by the condensation of o-phenylenediamine with 4-bromophenoxy acetic acid and product obtained was alkylated at the benzimidazole -NH with different electrophilic reagents. Subsequent reactions of the products by the Suzuki Coupling between benzimidazole derivatives and phenylboronic acid derivatives were accomplished. All these compounds were characterized by FT-IR, 1H NMR, MS and elemental analysis. These compounds were screened for their potential antibacterial and antifungal activities. This exhibited some promising results towards testing organism in-vitro.